Association between serum insulin-like growth factor-1 and bone mineral density in patients with type 2 diabetes - Zhao, Qianqian; Li, Youqian; Zhang, Qiuping; Zhang, Mei; Ban, Bo (Frontiers in Endocrinology, 2024)
Background: Secondary osteoporosis is associated with type 2 diabetes mellitus (T2DM), and there is conflicting evidence regarding the relationship between insulin-like growth factor-1 (IGF-1) and bone mineral density (BMD) in different populations. The objective of this study was to investigate the relationship between serum IGF-1 levels and BMD in patients with T2DM. Method: A retrospective cross-sectional study was performed on a cohort of 363 patients with T2DM, comprising men aged over 50 and women who are postmenopausal. Those with no significant medical history or medication affecting BMD or IGF-1 were considered. Data analyzed included IGF-1 levels, markers of bone metabolism, and measurements of BMD. To account for age and gender variations, we calculated IGF-1 standard deviation scores (IGF-1 SDS) for further investigation. Results: A significant increase in BMD at lumbar spine (LS), femoral neck (FN), and total hip (TH) was observed as IGF-1 SDS tertiles rose. We revealed a nonlinear correlation between IGF-1 SDS and BMD at these sites, with a common inflection point identified at an IGF-1 SDS level of -1.68. Additionally, our multivariate piecewise linear regression analysis highlighted a positive association between IGF-1 SDS and BMD at LS, FN, and TH when IGF-1 SDS exceeded the inflection point (β 0.02, 95% CI 0.01, 0.04 for LS; β 0.02, 95% CI 0.01, 0.03 for FN; β 0.02, 95% CI 0.01, 0.03 for TH). Conversely, below the inflection point, this association was not significant (β -0.04, 95% CI -0.10, 0.01 for LS; β -0.04, 95% CI -0.08, 0.01 for FN; β -0.03, 95% CI -0.08, 0.01 for TH). Conclusion: These findings reveal a nonlinear relationship between IGF-1 SDS and BMD in T2DM patients. Higher serum IGF-1 levels were connected to increased bone density only after surpassing a certain threshold.